Keyword: addicted, non-addicted, personality characteristics, problem solving styles Prevalence of Narcotic Drugs Use among Physical Education and Non-Physical Education Female Students - Hamid Arazi; Bahman Asgari (Drug Control Headquarters, Research and Education Office, 2011)
Introduction: the purpose of this study was to investigate the prevalence of narcotic drugs use among female students field of physical education and non-physical education of Guilan University. Method: For doing this study, narcotic drugs use questionnaire was used. Questionnaires distributed among 240 subjects in two groups of female physical education students (n=100) and female non-physical education students (n=140) randomly. Findings: The results indicated that the rate of narcotic drugs use among female students of physical education and non-physical education was not significantly different. With regard to this point that some non-physical education students who had a reasonable level of physical activity, retest were again done between active and sedentary students and the results showed that smoking and alcohol use between active and sedentary students were significantly different. Conclusion: According to results, exercise at universities especially in population of female students may prevent the growing trend of narcotic drugs use in this stratum of society.